The successful clinical outcomes of pregnant women with advanced chronic kidney disease - Ji-Yeun Chang; Hanbeol Jang; Byung Ha Chung; Young-Ah Youn; In-Kyung Sung; Yong-Soo Kim; Chul Woo Yang (The Korean Society of Nephrology, 2016)
Background: Successful pregnancy outcomes in patients with advanced chronic kidney disease (CKD) are increasingly common in Western countries. However, in Korea, the available literature addressing this clinical issue is scarce. Methods: We reviewed 5 successful parturitions [1 patient with Stage 5 CKD and 4 with maintenance hemodialysis (HD)] at Seoul St. Mary's Hospital over 3 years and investigated changes in dialysis prescription, anemia management, and the incidence of maternal and neonatal complications. Results: There were no maternal or neonatal deaths in this cohort. The mean age at the time of conception and delivery was 35.8 ± 3.7 and 36.2 ± 3.5 years, respectively. Dialysis patients received more frequent and intensified HD during pregnancy, 20.0 ± 5.7 h/wk of HD over 5 visits with the ultrafiltration dose maintained between 1 and 2 kg per session. All patients received erythropoietin-stimulating agents and iron replacement therapy during pregnancy. The mean hematocrit was 33.1 ± 1.9% before pregnancy and was well maintained during gestation (33.9 ± 3.8% at the first trimester, 29.2 ± 4.2% at the second trimester, and 33.6 ± 8.7% at delivery). The mean gestation period was 32.7 ± 4.7 weeks, with 60% of patients experiencing premature delivery. The primary maternal complication was pre-eclampsia; 3 women developed pre-eclampsia and underwent emergency cesarean sections. Most neonatal complications were related to preterm birth. Conclusion: Dialysis-related care and general clinical management improved the clinical outcome of pregnancy for patients with advanced CKD.